11 Å tobermorite ion exchanger from recycled container glass. (26th September 2011) - Coleman, Nichola J.
Waste container glass cullet has been evaluated as a feedstock material for the hydrothermal synthesis of tobermorite, a cation exchanger. Accordingly, it is demonstrated that essentially phase-pure 11 Å tobermorite, Ca5 Si6 O16 (OH)2 · 4H2 O, can be obtained from a stoicheiometrically-adjusted mixture of waste glass cullet and calcium oxide in aqueous sodium hydroxide at 100ºC. A batch sorption study indicated that the cullet-derived tobermorite is highly effective in the removal of Pb 2+ (1.66 mmol g –1 ) and Cd 2+ (0.48 mmol g –1 ) from solution. Its ion exchange characteristics are compared with those of other waste-derived sorbents and potential applications are discussed.